2008
DOI: 10.1007/s00467-007-0651-7
|View full text |Cite
|
Sign up to set email alerts
|

Which cystography in the diagnosis and grading of vesicoureteral reflux?

Abstract: The gold standard procedure for the evaluation of vesicoureteral reflux (VUR) is the radiographic voiding cystourethrography (VCUG); direct radionuclide voiding cystography (DRVC) is an alternative method for detecting VUR. A new imaging procedure, voiding urosonography (VUS) with contrast medium, has recently been introduced. We have carried out a comparative study of these three techniques in 157 patients (aged 6 weeks-4.7 years). VUS showed the presence of VUR in 91 of 311 renal units; VCUG detected reflux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In previous studies, the mean examination time for ce-VUS was between 8 and 34 minutes, depending on the contrast product and ultrasound modality used [4, 6, 12, 13]. Hence, the phenomenon of premature microbubble destruction cannot be explained by a longer examination time in our centre as compared to other groups.…”
Section: Discussionmentioning
confidence: 73%
“…In previous studies, the mean examination time for ce-VUS was between 8 and 34 minutes, depending on the contrast product and ultrasound modality used [4, 6, 12, 13]. Hence, the phenomenon of premature microbubble destruction cannot be explained by a longer examination time in our centre as compared to other groups.…”
Section: Discussionmentioning
confidence: 73%
“…Although it has higher sensitivity and specificity (86 and 91.3%, respectively), it often fails to demonstrate the fistulous tract [2,3,5,7,8]. In our case, the CT findings were evaluated as 'suspicious'.…”
Section: Discussionmentioning
confidence: 91%
“…The options include plain abdominal radiography, IVP and US examination, BE, CT, MRI and cystoscopy [3,5]. Garcea et al stated in their study that the sensitivity of plain abdominal radiography was 29%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Radionuclide cystograms have also been utilized due to their lower radiation exposure and higher sensitivity; however, the anatomical depiction is less precise and does not allow for initial, highresolution grading of disease severity. 7 used to diagnose a suspected episode of acute pyelonephritis and later to assess differential renal function and the degree of renal cortical scarring 8 ( Figure 7). Urodynamic studies are only indicated in children suspected to have secondary reflux.…”
Section: Epidemiology and Etiologymentioning
confidence: 99%